The effect of concentration to the crystallinity and ferroelectric of thin PVDF-TrFE (72/28) film / Mohd Syamsul Redzuan Basirun - Basirun, Mohd Syamsul Redzuan (2009)
PVDF-TrFE is a ferroelectric copolymer with a strong piezoelectric effect, and is widely used in broad range of applications in electronic and micromechanical system. In many of these applications such as data storage and memory devices, the thickness of the polymer films were reduced so as to reduce operation voltage. However the thickness of the film is limited by the ferroelectric response. In this study, different concentration of PVDF-TrFE (72/28) of 0.25g/ml, 0.20g/ml, 0.15g/ml, O.lOg/ml and 0.05g/ml were used. The thin films were spin coated and was annealed with a hot plate at temperature (160±1) °C. The film thickness was determined using a Field Emission Scanning Electron Microscopy (FESEM). The crystal form was characterized using Polarized Light Optical Microscopy (PLOM), Field Emission Scanning Electron Microscopy (FESEM) and Fourier Transform Infrared (FTIR). The solution concentration of 0.25g/ml produces thicker PVDF-TrFE (72/28) copolymer film whilst the spinning parameter had insignificant contribution to the thickness of the film. The PVDF-TrFE (72/28) copolymer film showed an increase in the amount of crystal and crystal size at 0.25g/ml. The orientation of crystal of the film was found to be scatter Jind there was no alignment of crystal.